MEMBUMIKAN PENDIDIKAN MULTIKULTURAL DALAM BINGKAI PENDIDIKAN ISLAM - Zaedun Na’im (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2020)
ABSTRACTThis discussion is about what efforts are made so that in the implementation of Islamic education in educational institutions can be more emphasized and practice the values of cultural diversity that are owned by students. Because this has become very important and very useful for students to further educate the early generations of the nation's future, so that one day they can continue to be embedded in their souls of the importance of respecting cultural diversity in the community so that it will strengthen the unity and integrity of the Indonesian nation. Problems or constraints experienced in the implementation of Islamic education is how to find the right formula or form in the realization of planting and habituation of multicultural values in students themselves. If this can be fulfilled then it will ground multicultural education based on Islamic education then it can be realized. In this study the writer uses qualitative research with a library study approach or library research and is descriptive in nature, where the writer wants to reveal more deeply the concepts or ways in order to realize the slogan or the term